Pengaruh Pengembangan Karier dan Kompensasi Terhadap Kinerja Auditor Melalui Budaya Organisasi sebagai Variabel Intervening - Melani, Elda; Wibowo, Imam; Latukismo, Tatag Herbayu (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine and analyze the influence of Career Development and Compensation on Auditor Performance through Organizational Culture as An Intervening Variable. This study was conducted at the Inspectorate General of the Ministry of Agrarian and Spatial Planning/National Land Agency. The sample size in this study is equal to the total population, which consists of 101 (one hundred and one) auditors. The data analysis method used in this study is Partial Least Square Modeling (PLS). The results of the study indicate that (1) career development has a positive and significant influence on auditor performance, (2) compensation has a positive and significant influence on auditor performance, (3) career development has a positive and significant influence on organizational culture, (4) compensation has a positive and significant influence on organizational culture, (5) organizational culture has a positive and significant influence on auditor performance, (6) career development has a positive and significant influence on auditor performance through organizational culture, and (7) compensation has a positive and significant influence on auditor performance through organizational culture.